Enhanced stress and changes to regional seismicity due to the 2015 Mw 7.8 Gorkha, Nepal, earthquake on the neighbouring segments of the Main Himalayan Thrust - Chan, Chung-Han (2017)
In this study we evaluate stress evolution and change in seismic hazard after the 2015 Gorkha earthquake sequence. We take a methodology usually used in areas with well-established seismic monitoring and apply it to an area with a sparse dataset and a limited time observation window. Our goal is to validate this approach as a rapid response tool for seismic forecasting after large earthquakes. We propose a long-term seismic forecasting model of the Main Himalayan Thrust using the historical earthquake catalogue and regional paleo-seismicity. Through application of the rate-and-state friction model, we evaluate short-term rate evolution after the Gorkha earthquake. The long elapsed time since the last megathrust event and the mainshock coseismic stress increase on the Main Himalayan Thrust suggest high seismic potential in the Lalitpur and Lamjung areas along the fault system. We also calculate the stress change on optimally oriented planes in the region and model the regional seismicity rate using a smoothing kernel method and seismicity since 1921. The location of the consequent earthquakes coincides with areas of high background seismicity rate and areas where stress was enhanced by the Mw 7.8 mainshock and Mw 7.3 aftershock. We model the change of seismic rate over time and project a fast decrease, due to the short aftershock duration assumption we use.